2007
DOI: 10.1097/shk.0b013e31804d415f
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Long Chain Myosin Light Chain Kinase (Mlck-210) in Microvascular Hyperpermeability During Severe Burns

Abstract: Microvascular leakage has been implicated in the pathogenesis of multiple organ dysfunction during trauma. Previous studies suggest the involvement of myosin light chain (MLC) phosphorylation-triggered endothelial contraction in the development of microvascular hyperpermeability. Myosin light chain kinase (MLCK) plays a key role in the control of MLC-phosphorylation status; thus, it is thought to modulate barrier function through its regulation of intracellular contractile machinery. The aim of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 30 publications
5
53
0
Order By: Relevance
“…Introduction of constitutively active MLCK into coronary venular endothelial cells increased phosphorylation of MLC and increased transendothelial flux of albumin across endothelial monolayers (58). Mice with an endothelial-specific knockout of MLCK (MLCK210) have reduced microvascular hyperpermeability in models of atherosclerosis or in response to severe burns (61, 62). However, another study with endothelial-specific MLCK-knockout mice found that the increase of microvascular endothelial permeability in response to lipopolysaccharides was not dependent on MLCK(63), in agreement with our study here.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of constitutively active MLCK into coronary venular endothelial cells increased phosphorylation of MLC and increased transendothelial flux of albumin across endothelial monolayers (58). Mice with an endothelial-specific knockout of MLCK (MLCK210) have reduced microvascular hyperpermeability in models of atherosclerosis or in response to severe burns (61, 62). However, another study with endothelial-specific MLCK-knockout mice found that the increase of microvascular endothelial permeability in response to lipopolysaccharides was not dependent on MLCK(63), in agreement with our study here.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which eNOS internalization and NO production, possibly via soluble guanylyl cyclase, modify junctional proteins to induce hyperpermeability to proteins remain unresolved. It is plausible that NO production in the cytosol may influence cytoskeletal proteins; thus, promoting EC contraction and hyperpermeability (20)(21)(22). One may alternatively speculate that NO-driven S-nitrosylation of proteins may induce changes in trafficking and permeability.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, this retraction is linked to endothelial permeability enhancement and vascular leakage under proinflammatory conditions. In this context, an activation of the nmMLCK has been linked to several pathophysiological conditions, such as vascular inflammation and atherosclerosis,18 acute lung injury,19 endotoxic shock,20 and severe burns 21…”
Section: Introductionmentioning
confidence: 99%